LEXIKOLOGIE UND ENTLEHNUNGEN IN MODERNEN SPRACHEN (Web of Teachers: Inderscience Research, 2025)
Globalization has led to an active borrowing of words and expressions between languages. The article examines the lexical changes that occur as a result of this process, as well as the cultural and social factors that contribute to borrowing. Examples of borrowings from English into other languages and their adaptation to phonetic and grammatical systems are considered. The consequences of borrowing for linguistic identity and cultural heritage are also discussed.